Prognozowanie demograficzne dla małych obszarów na przykładzie miasta Poznania w latach 2005-2030 - Paradysz, Jan (Demographic forecast of small area. Case of Poznan city between 2005 and 2030, 2006)
This paper deals with demographic projection of small areas such as urban districts in big cities. In similar cases the use of traditional projection methods leads to some prediction errors due to low population numbers. On the other hand demographic projections for the specific urban areas create an opportunity to use auxiliary information about local area development plans and other intended actions of the local authorities. This kind of information is difficult to use in the scale of the whole country or large regions. Therefore for the demografie prediction we suggest the adaptation of the methods used with small areas. To carry out the verification of the method we chose the city of Poznan. We based our research on the information about reserves in building industry in individual urban units provided by the City Urban Workshop.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 17-33